“Influencia del ciberacoso/ciberbullying en el estado emocional de estudiantes de octavo grado de la Unidad Educativa Marieta de Veintimilla” - Jiménez González, Lizbeth Maricela (2022)
The present research work called “Influence of ciberbullying/ciberbullying on the emotional state of eighth grade students of the Marieta de Veintimilla Educational Unit, aimed to theoretically define the forms of ciberbullying/ciberbullying that affect the emotional state of students of eighth grade students of the institution. This research a with qualitative and quantitative methodological approach of non-experimental design in which the scientific, inductive-deductive, analytical and synthetic method was used for the collection of bibliographic information, in addition to the data collection the survey technique was used, the interview, in which eighth grade students of upper 75 eighth grade students of upper basic participated. The most outstanding results show that this type of violence such as ciberbullying/ciberbullying does not exist in the institution, however it is important to pay attention to the minority of students who carry out these acts of violence since they can rise and represent a risk to others, it is also evident that the majority of students recognize that ciberbullying/ciberbullying affects emotionally at the school, family and social level, that is, they are aware of the negative effects and consequences of carrying of these kinds of acts. In this way, it is concluded that ciberbullying/ciberbullying in eighth grade students of the Marieta Educational Unit is not presenting ciciberbullying/ciberbullyin.itself in great magnitude, but they do recognize that this phenomenon affects their emotional state in any area of their life. Therefore, it is necessary to propose a proposal based on emotional workshops to eradicate ciberbullying/ciberbullying. Key words: emotional education, harasser or aggressor, victim and spectator.